Strengthening Potential Sectors, Growth Centers, and Regional Financial Capacity in Efforts to Increase Economic Growth in West Sumba Regency - Bili, Sisilia Arista; Sumanto, Agus (Perpustakaan dan Penerbitan Unismuh Makassar, 2022)
This study aims to find out in detail the cause of an area being categorized as a disadvantaged area (3T). The object of this research is West Sumba Regency, which is one of the underdeveloped areas of the 22 regencies/cities in NTT. The type of data used is secondary data sourced from BPS publications and West Sumba Regency APBD data for the 2016-2020 period. This study uses six analytical techniques, four of which are SLQ, DLQ, Shift Share, and Klassen Typology which are then overlaid to find out which sectors are the leading economic sectors and have potential in the future. Scalogram analysis to determine the area that is the center of growth based on its facilities and accessibility. Regional Financial Analysis to find out how much the government is able to manage regional financial resources autonomously. The results showed that there were only 3 basic sectors while the other 11 entered as potential sectors. Waikabubak City and Wanokaka District are the areas with the highest growth centers during the 2016-2020 period. Based on regional financial analysis with 4 indicators that have been calculated, it shows that all of them are in the very less and less category with an instructive relationship pattern. This means that the level of dependence of the West Sumba district on the central government and other external parties is still very high in the 2016-2020 period